Analisis Faktor yang Mempengaruhi Tingkat Literasi Keuangan di Kalangan UMKM Kota Tegal (Universitas Negeri Semarang, 2015)
Based on preliminary research literacy level of SMEs owners in the Tegal city is still relatively low. Factors that affecting the level of literacy consists of gender, education level and income level. This research is a survey research. The results showed the level of literacy in the Tegal city SMEs owners are in the high category with an average of 11.79. Gender and education level factors affect the level of financial literacy owners of SMEs. Men SMEs owners and above the level of compulsory education have higher literacy level compared to women and under compulsory education. The income factor does not affect the level of financial literacy owners of SMEs. The owners of SMEs are suggested increase their knowledge aboout finance and governement can give education about finance.